Catalytic ethanolysis of Dahuangshan lignite and directional upgrading of two derived soluble mixtures. (1st November 2021) - Liu, Guang-Hui; Kang, Yu-Hong; Gao, Yong; Li, Yan-Jun; Ma, Xiang-Rong; Dang, Rui; Yan, Long; Yan, Wei-Wei; Bai, Hong-Cun; Zong, Zhi-Min; Wei, Xian-Yong
Graphical abstract: Highlights: The transfer of free radicals is essential for the cleavage of bridged bonds. SPs rich in alkanes and arenes can be obtained by CE. ESPC with fewer HAs is more suitable for upgrading to CLFs through CHC. Hydrocarbon- & phenol-rich portions can be rapidly separated by TMS extraction. Abstract: An in-situ and ex-situ cascade upgrade strategy was designed and used for upgrading Dahuangshan lignite-derived soluble mixtures (LDSMs) to obtain value-added chemicals and clean liquid fuels (CLFs), respectively. In the H2 -free catalytic ethanolysis, Ni/mordenite can effectively activate ethanol and promote the transfer of various free radicals including H·, CH3 CH2 ·, and CH3 CH2 O·, which synchronously facilitates the cleavage of bridged bonds in Dahuangshan lignite and the in-situ removal of heteroatoms (HAs) from LDSMs. As a result, the total yield of LDSMs increased from 40.6 to 66.5 wt%, wherein that of ethanol-soluble portion (ESP) increased from 21.4 to 32.4 wt%. Interestingly, alkanes and arenes with higher relative content (RC, 38.1%) were detected in ESPC (for catalytic ethanolysis), while arenols (24.7%) dominate ESPN (for ethanolysis). The analysis with a quadrupole exactive orbitrap mass spectrometer further confirmed the significant decrease in the relative abundance of HAs, especially O x class species, in ESPC . In addition, ESPN and ESPC with different properties were further used for enriching derived chemicals and for obtaining CLFs by catalytic hydroconversion (CHC), respectively. After the CHC, the total RCs of alkanes and cyclanes in the soluble portion (SP) are as high as 71.3%, and the content of HA-containing organic compounds was further decreased. Therefore, such SP containing less HAs is an attractive CLF precursor. A ternary mixed solvent was also designed for rapidly separating the SP from ESPN . The total RC of alkanes and arenes in PE5 as well as arenols in M5 are as high as 79.4 and 70.9%, respectively. Molecular dynamics simulations were further used to reveal the rapid enrichment mechanisms with ternary mixed solvents.